Sabq Al-Islam Ta’rikhiyyan wa Tafawuqahu fi Irsa’ Huquq Al-Insan (Dirosah Muqoronah Baina At-Tsyri’i Al Islamiy wa An Nadzmi Al Wadl’iyah) - Yousif Abdallah Mustafa Abdalrazeq (UIN Maulana Malik Ibrahim Malang, 2017)
هذه دراسة تدور محاورها حول التشريع الإسلامي والنظم الوضعية. هدفت الدراسة إلى إبراز دور الإسلام التأريخي في إرساء حقوق الإنسان، انتهجت الدراسة المنهج الاستقرائي التحليلي، وتناولت الدراسة الموضوع بالبحث والتحليل معتمدةً في ذلك على التشريع الإسلامي وما جاءت به الحضارة الإسلامية التي سادت العالم، ذلك بأن التشريع الإسلامي إلهي المصدر وصالح لكل زمان ومكان، على عكس النظم الوضعية التي تتحدث عن قضية الساعة، وقد استشهدت الدراسة بمجموعة من أقوال رجال النظم الوضعية مقارنة في موضوع البحث التي ظهر من خلالها تفوق التشريع الإسلامي بصورة واضحة نالت إعجاب واعتراف كثير من العلماء والمفكرين في العالم. This study covers Islamic law and positive law, which aims to show the role of Islam in the history of establishing human rights. It employs inductive analytic approach. Hence, it mainly refers to the law of Islam (Islamic tasyri') and what is brought by Islamic civilization leading the world. It is due to the fact that Islamic tasyri’ comes from Allah and is worth of all time and place. On the contrary, the positive law made by man deals with the problems related to time and conditions. This study is supported by legal experts to compare both laws. The finding shows the obvious advantage of Islamic tasyri' rather than other regulation or positive law. Its overwhelming advantage is also confirmed by world legal experts